Traceability Matrix for Effort Estimation in Change Request - Mazidah Mat Rejab; Nurulhuda Firdaus Mohd Azmi; Suriayati Chuprat; Hairulnizam Mahdin (Penerbit UTHM, 2023)
In the last decade, the management of IT projects has become a challenging task. The latest published figures on the status of IT projects indicate a large failure rate, which has created a crucial challenge for project managers. In maintenance phase, the impact of changes is an important aspect due to the evolving environment of the software development life cycle. The aim of this book is to investigate the need and significant use of the traceability matrix for effort estimation to accommodate changes request in maintenance tasks. Change request is necessary to keep task current and reusable. Software evolves over time due to specific changes during development and maintenance at every point, the management aspect of modifications can become more complicated and potentially risky. Many of the current traceability approaches and tools are devoted to and restricted to high-level objects such as specifications and fewer capabilities made available to handle lowerlevel artefacts such as classes and codes While effort estimates have been in place for decades, it remains a major challenge for project management to make accurate estimates and, ultimately, to successfully complete the IT project.